A coplanar waveguide‐fed broadband circularly polarized microstrip antenna for conformal applications. Issue 3 (13th January 2021) - Yang, Zhengkun; Kou, Na; Yu, Shixing; Ding, Zhao; Zhang, Zhengping
Abstract: A broadband circularly polarized conformal microstrip antenna based on coplanar waveguide feeding is presented. By embedding a pair of disturbing branches on a rectangular grounded metal ring and protruding into the ring a pentagonal monopole, the measured bandwidths of 3‐dB axial ratio and 10‐dB impedance achieve 58.5% (4.6 to 8.4 GHz) and 67.7% (4.3 to 8.7GHz), respectively. The antenna has a small form factor, a low profile and low manufacturing costs. Simulated and measured results indicate that this antenna has excellent adaptability to cylindrical carriers with different radius, which is adapted for potential conformal applications. In addition, the proposed antenna can find applications in WLAN (5, 5.2, and 5.8 GHz), WiMAX (5.5GHz), and other C‐band (4GHz‐8GHz) wireless communications.